Surgical management of peritoneal metastasis: Opportunities for pharmaceutical research - Wientjes, Michael G.; Lu, Ze; Chan, Carlos H.F.; Turaga, Kiran; Au, Jessie L.S. (Journal of controlled release, 2023)
Cytoreductive surgery (CRS) has emerged as a survival-extending treatment of peritoneal metastasis (PM); recent advances include using intraperitoneal chemotherapy (IPC) at normothermic or hyperthermic temperatures, or under pressure (CRS + IPC). Clinical CRS + IPC research has established its highly variable efficacy and suggested tumor size, tumor locations and presence of ascites as potential determinants. On the other hand, there is limited knowledge on the effects of pharmaceutical properties on treatment outcomes. The present study investigated the inter-subject variability of paclitaxel binding to proteins in patient ascites because some PM patients show accumulation of ascites and because activity and transport of highly protein-bound drugs such as paclitaxel are affected by protein binding. Ascites samples were collected from 26 patients and investigated for their protein contents using LC/MS/MS proteomics analysis and for the concentrations of total proteins and two major paclitaxel-binding proteins (human serum albumin or HSA and α-1-acid glycoprotein or AAG). The association constants of paclitaxel to HSA and AAG and the extent of protein binding of paclitaxel in patient ascites were studied using equilibrium dialysis. Proteomic analysis of four randomly selected samples revealed 288 proteins, >90% of which are also present in human plasma. Between 72% - 94% of paclitaxel was bound to proteins in patient ascites. The concentrations of HSA and AAG in ascites showed substantial inter-subject variations, ranging from 14.7 – 46.3 mg/mL and 0.13–2.56 mg/mL, respectively. The respective paclitaxel association constants to commercially available HSA and AAG were ∼ 3.5 and ∼ 120 mM. Calculation using these constants and the HSA and AAG concentrations in individual patient ascites indicated that these two proteins accounted for >85% of the total protein-binding of paclitaxel in ascites. The extensive drug binding to ascites proteins, by reducing the pharmacologically active free fraction, may lead to the diminished CRS efficacy in PM patients with ascites. Clinical advances in CRS + IPC have outpaced current knowledge of pharmaceutical properties in this setting. IPC, as a locally acting therapy, is subjected to processes different from those governing systemic treatments. This study, to our knowledge, is the first to illustrate the implications of drug properties in the CRS + IPC efficacy against PM. While drugs are now an integral part of PM patient management, there is limited pharmaceutical research in this treatment setting (e.g., effects of hyperthermia or pressure on drug transport or release from delivery systems, pharmacokinetics, pharmacodynamics). Hence, CRS + IPC of PM represents an area where additional pharmaceutical research can assist further development and optimization. [Display omitted] •Peritoneal metastasis is managed by surgery+intraperitoneal chemotherapy (CRS + IPC).•IPC efficacy against peritoneal metastasis appears lowered by presence of ascites.•Extensive protein binding of paclitaxel reduces % active free drug in patient ascites.•Albumin and α-1-acid glycoprotein account for >85% paclitaxel binding in ascites.•Current study is an example on using pharmaceutical research to optimize CRS + IPC.